Mekanisme Kerja Obat Antimalaria - Syamsudin Syamsudin (JURNAL ILMU KEFARMASIAN INDONESIA, 2005)
Malaria remains the most devastating infectious parasitic disease, inflicting both death and economic losses on at least half the world's population. Numerous attempts have been made to control the disease using vector control measures and/or chemoprophylaxis. Antimalarial drugs have a selective action on the different phases of the parasite life cycle. Mechanism of antimalarial drugs action will be discussed in this article.